Assessment of the menstrual cycle, eating disorders and self-esteem of Polish adolescents. (2nd January 2017) - Drosdzol-Cop, Agnieszka; Bąk-Sosnowska, Monika; Sajdak, Dominika; Białka, Agnieszka; Kobiołka, Agnieszka; Franik, Grzegorz; Skrzypulec-Plinta, Violetta
Abstract: Introduction: Eating disorders are an important factor in menstrual cycle disorders in girls. Moreover, low self-esteem among adolescent girls may be a risk factor for eating disorders. The aim of the study was to assess the menstrual cycle, eating habits and self-esteem of Polish adolescents. Methods: The study was conducted from January 2014 to March 2015 and included 623 girls, aged 15–19, from randomly selected junior high schools in Silesia, Poland, in which their menstrual cycle, risk of eating disorders and self-esteem were evaluated. A five-part questionnaire was used to assess basic demographic data, lifestyle and physical activity, gynecological history, as well as Rosenberg Self-Esteem Scale (SES) and Eating Attitude Test (EAT-26). Results: Irregular menstrual cycles were observed in 236 (37.88%) girls; 5.20% presented secondary amenorrhea. Based on the EAT-26 test, 101 (16.21%) girls were indicated being at risk for an eating disorder. Low self-esteem was observed in 340 (54.57%) study girls on the base of SES. Discussion: Girls with irregular menses had higher scores on the EAT-26 test in subscales: EAT-overall score, EAT-diet and EAT–bulimia, while lower scores on the SES. In our study, we did not observe a significant relationship between exercise intensity, body mass, BMI and menstrual cycle regularity. Low self-esteem among adolescent girls may be a risk factor for eating disorders which could interrupt the menstrual cycle.